Plasmodium kinases as targets for new-generation antimalarials. (December 2012) - Lucet, Isabelle S; Tobin, Andrew; Drewry, David; Wilks, Andrew F; Doerig, Christian
There is an urgent need for the development of new antimalarial drugs with novel modes of actions. The malarial parasite, Plasmodium falciparum, has a relatively small kinome of <100 kinases, with many members exhibiting a high degree of structural divergence from their host counterparts. A number of Plasmodium kinases have recently been shown by reverse genetics to be essential for various parts of the complex parasitic life cycle, and are thus genetically validated as potential targets. Implementation of mass spectrometry-based phosphoproteomics approaches has informed on key phospho-signalling pathways in the parasite. In addition, global phenotypic screens have revealed a large number of putative protein kinase inhibitors with antimalarial potency. Taken together, these investigations point to the Plasmodium kinome as a rich source of potential new targets. In this review, we highlight recent progress made towards this goal.